Microcirculatory tissue oxygenation correlates with kidney function after transcatheter aortic valve implantation–Results from a prospective observational study - Dietrich, Maximilian; Antonovici, Ana; Hölle, Tobias; Nusshag, Christian; Kapp, Anne-Christine; Studier-Fischer, Alexander; Arif, Rawa; Nickel, Felix; Weigand, Markus Alexander; Frey, Norbert; Lichtenstern, Christoph; Leuschner, Florian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Kidney dysfunction is common in patients with aortic stenosis (AS) and correction of the aortic valve by transcatheter aortic valve implantation (TAVI) often affects kidney function. This may be due to microcirculatory changes. Methods We evaluated skin microcirculation with a hyperspectral imaging (HSI) system, and compared tissue oxygenation (StO2), near-infrared perfusion index (NIR), tissue hemoglobin index (THI) and tissue water index (TWI) in 40 patients undergoing TAVI versus 20 control patients. HSI parameters were measured before TAVI (t1), directly after TAVI (t2), and on postinterventional day 3 (t3). The primary outcome was the correlation of tissue oxygenation (StO2) to the creatinine level after TAVI. Results We performed 116 HSI image recordings in patients undergoing TAVI for the treatment of severe aortic stenosis and 20 HSI image recordings in control patients. Patients with AS had a lower THI at the palm (p = 0.034) and a higher TWI at the fingertips (p = 0.003) in comparison to control patients. TAVI led to an increase of TWI, but had no uniform enduring effect on StO2 and THI. Tissue oxygenation StO2 at both measurement sites correlated negatively with creatinine levels after TAVI at t2 (palm: ρ = −0.415; p = 0.009; fingertip: ρ = −0.519; p < 0.001) and t3 (palm: ρ = −0.427; p = 0.008; fingertip: ρ = −0.398; p = 0.013). Patients with higher THI at t3 reported higher physical capacity and general health scores 120 days after TAVI. Conclusion HSI is a promising technique for periinterventional monitoring of tissue oxygenation and microcirculatory perfusion quality, which are related to kidney function, physical capacity, and clinical outcomes after TAVI. Clinical trial registration https://drks.de/search/de/trial, identifier DRKS00024765.